PENINGKATAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN MENGGUNAKAN TEAM ASSISTED INDIVIDUALIZATION KELAS V SEKOLAH DASAR NEGERI 03 KAWAN BENGKAYANG - Sunarti, Sunarti; Rosnita, Rosnita; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakThe research problem is whether there is an increase in student learning outcomes in learning Citizenship Education using Team Assisted Individualization model in class V Public Elementary School 03Kawan Bengkayang Regency. Research aims to improve student learning outcomes through the use of Team Assisted Individualization model. The method used in this research is descriptive method in the form of Classroom Action Research, is collaborative. Data collection techniques used are the technique of direct observation and measurement by means of data collection is the Student Worksheet. Setting research with subject Teachers / Researchers and students of class V amounted to 28 students.The results of the three cycles obtained are: 1) Ability and planning of learning from cycle I and cycle II are 3.07 and 3.46 increasing by 0.39 which is included in the good category and the third cycle is 3.74 increasing by 0.28 in the excellent category. 2) The ability and implementation of learning from cycle I and cycle II are 2.83 and 3.37, increasing by 0.54 which is in the good category and the third cycle also increases by 0.24 so it becomes 3.61 and is very good category. 3) Learning outcomes of students in the first cycle of 48.85 with a low category experienced an increase of 17.86 in the second cycle to 60.71 in the medium category and in the third cycle increased by 14.29 to 75 in the high category.Conclusion: learning outcomes of students have increased in each cycle where the results of students are in good category.Suggestion: The teacher is expected to be able to use the team assisted individualization learning model in improving the learning outcomes of students in the future. Keywords: Improved Learning Outcomes of Students, Model Team Assisted Individualization, Citizenship Education.